The Fire is Coming: An HIV Prevention Intervention Contextualized to the Maasai People of Tanzania - Holly Freitas; Marcia A Nayak (Health for All Nations, 2014)
"The Fire is Coming" film is an innovative HIV-prevention intervention contextualized to the Maasai people of Tanzania through use of a traditional Maasai story. The intervention was developed and implemented in partnership with Maasai Pastoralists for Education and Development (MAPED). Although there have been numerous Knowledge-Attitude-Practice (KAP) surveys conducted among the Maasai, this is the first control-group comparison study designed to measure the effectiveness of an HIV-prevention intervention contextualized specifically to the Maasai people of Tanzania. We will first discuss the background and context in which the intervention was developed and methods used to develop the intervention. We will then discuss the evaluation methods, results, and implications of a retrospective Knowledge, Attitudes, Practices (KAP) two-village comparison survey (n=200) for "The Fire is Coming" HIV-prevention intervention among Maasai people. There was a significant effect for HIV-related attitudes, t(16) = 2.77, p <0.05, regarding willingness to care for an HIV infected person, willingness to be tested for HIV, self-efficacy toward HIV-prevention, married women's ability to use condoms, unmarried girls' ability to refuse high-risk sexual behaviors, married men's ability to use condoms, and married men's ability to limit sex to their spouses. There was a significant effect for HIV-related behavior changes, t(8) = 2.89, p <0.05, with reported family decisions made, esoto (the ritualized sexual initiation of pre-pubescent girls) stopped, sexual behaviors changed, blade-sharing stopped, and other traditional custom changes reported. Although knowledge rates were often higher in the intervention area than in the comparison area, there was no significant difference in HIV-related knowledge, t(12)=1.85, p >0.05. Implications: Belief in one's ability to do something is often the pivotal point for behavior change. The results of the survey denote a highly effective intervention in changing HIV-related attitudes and behaviors. It is promising for replication among other Maasai communities and for adaptation with indigenous people groups in other regions.